2022
DOI: 10.1111/cts.13229
|View full text |Cite
|
Sign up to set email alerts
|

Effect of enzalutamide on PK of P‐gp and BCRP substrates in cancer patients: CYP450 induction may not always predict overall effect on transporters

Abstract: Drug-drug interaction (DDI) is an important consideration for clinical decision making in prostate cancer treatment. The objective of this study was to evaluate the effect of enzalutamide, an oral androgen receptor inhibitor, on the pharmacokinetics (PK) of digoxin (P-glycoprotein [P-gp] probe substrate) and rosuvastatin (breast cancer resistance protein [BCRP] probe substrate) in men with metastatic castration-resistant prostate cancer (mCRPC). This was a phase I, open-label, fixed-sequence, crossover study (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…As enzalutamide showed both P-gp inhibition and induction effects in in vitro studies, a clinical DDI study would only reveal the net effect on P-gp. The clinical net effect of enzalutamide on P-gp was investigated with a typical P-gp substrate, digoxin [ 3 ]. Multiple oral administration of 160 mg of enzalutamide increased digoxin AUC and C max by 29% and 17%, respectively, indicating enzalutamide’s inhibition effect on P-gp outweighed its induction effect.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As enzalutamide showed both P-gp inhibition and induction effects in in vitro studies, a clinical DDI study would only reveal the net effect on P-gp. The clinical net effect of enzalutamide on P-gp was investigated with a typical P-gp substrate, digoxin [ 3 ]. Multiple oral administration of 160 mg of enzalutamide increased digoxin AUC and C max by 29% and 17%, respectively, indicating enzalutamide’s inhibition effect on P-gp outweighed its induction effect.…”
Section: Discussionmentioning
confidence: 99%
“…Under these assumptions, C max ratio was slightly overpredicted which may be a representation of stronger induction or weaker inhibition of intestinal P-gp in the clinical setting compared to model assumptions. In the clinical study, a decrease in renal clearance of digoxin was observed in the presence of enzalutamide, which may be a result of enzalutamide’s inhibitory effect on renal P-gp, which is not accounted for in the present PBPK analysis [ 3 ]. Since inhibition of renal P-gp results in an increase in AUC only, not incorporating this mechanism into the model could be a possible reason for overestimation in the C max ratio.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro DDI studies have indicated that enzalutamide is an inhibitor of P-gp and BCRP [ 34 ], and it has been suggested to have the potential for transporter-mediated DDIs via interactions with P-gp and BCRP when coadministered to patients with medications that are substrates of these efflux transporters [ 35 ]. In addition, enzalutamide could potentially induce P-gp and BCRP as it is a strong inducer of CYP3A4 and because both transporters and CYP3A4 are induced by PXR [ 22 , 24 , 36 ].…”
Section: Enzalutamidementioning
confidence: 99%